Historical dictionary of Saudi Arabia - Peterson, J. E. (Lanham : Rowman & Littlefield Publishing Group, 2020)
'This third edition of Historical Dictionary of Saudi Arabia contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture'--
Sumbangan Ezad Azraai Jamsari.
Keywords: Saudi Arabia -- History -- Dictionaries